Development Of Antibacterial Chitosan-Based Wound Dressing Incorporated With Zno/Cuo Nanoparticles Using Calotropis Gigantea - Govindasamy, G Ambarasan (2023)
In this work, ZnO/CuO nanocomposites incorporated in chitosan (Cs) based biopolymer were studied for physicochemical, antibacterial, cytocompatibility and wound healing profiles. This ZnO/CuO-Cs nanocomposites were obtained by freeze-thawing process and characterized by XRD, SEM, TEM, EDAX, FTIR, AAS, ICP and UV-vis spectroscopy.